2014
DOI: 10.1016/j.enpol.2014.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Unseen influence—The role of low carbon retrofit advisers and installers in the adoption and use of domestic energy technology

Abstract: Abstract:Reducing climate changing emissions associated with residential property continues to be a significant challenge. Five case studies of different domestic energy technology schemes in England highlight the influence of advisers and installers in househol carbon technologies. Many of these advisers and installers are micro-enterprises working in connected groups in particular geographic areas. Such micro-enterprises form a large part of the construction sector, but despite the number of enterprises and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 32 publications
3
74
0
2
Order By: Relevance
“…Particularly, the home renovation market is still largely dominated by micro-enterprises offering single products or services, some of which are even beyond the reach of current policy (Owen et al 2014). This can bring knowledge gaps, uncertainty on who is responsible and poor communication, ultimately resulting in a design-performance gap (Killip et al 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Particularly, the home renovation market is still largely dominated by micro-enterprises offering single products or services, some of which are even beyond the reach of current policy (Owen et al 2014). This can bring knowledge gaps, uncertainty on who is responsible and poor communication, ultimately resulting in a design-performance gap (Killip et al 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Intermediaries' influence is related to their technical and social capacities [30] so successful transformation of our built environment to support reduced energy use will require changes in installer and adviser behaviour, reflecting the particular socio-technical challenges of current homes and households.…”
Section: Implications For the Indoor And Built Environmentmentioning
confidence: 99%
“…Before installation begins, even before retrofit measures have been identified and specified, decisions to incorporate new energy technologies into the home, and how to use them, are shaped by the advice and action of several intermediaries, including energy efficiency advisers and technology installers [30]. Nosberger et al [31] discuss the professionalisation of retrofit work and suggest that the required competences or capacities of these actors in the retrofit industry need to cover not only technical knowledge and skills, but personal and professional skills too.…”
Section: Role Of Intermediaries In Retrofitmentioning
confidence: 99%
“…Intermediaries such as plumbers, electricians, and energy-efficiency advisers have been additionally found to play key roles in residents' approaches to technology engagement [32]. In a comparative case study involving five schemes across England, Owen et al [32] suggested that greater attention in policy-making needs to be paid to the role microgeneration advisors have on the ways that residents decide to adopt energy-efficient technologies.…”
Section: Resident Behaviour and Interaction With Energy-efficient Heamentioning
confidence: 99%
“…In a comparative case study involving five schemes across England, Owen et al [32] suggested that greater attention in policy-making needs to be paid to the role microgeneration advisors have on the ways that residents decide to adopt energy-efficient technologies. Wade et al [33] similarly discussed the role plumbing merchants have in heating installers' decision-making regarding choices relating to systems and associated energy-efficient heating technologies.…”
Section: Resident Behaviour and Interaction With Energy-efficient Heamentioning
confidence: 99%